Electron-impact dissociative excitation cross sections for singlet states of molecular hydrogen - Tapley, J.; Scarlett, Liam; Savage, J.; Fursa, Dmitry; Zammit, M.; Bray, Igor (2018)
We report cross sections for electron-impact dissociative excitation of the B 1 Σ + u , C 1 Π u , D 1 Π u , B ′ 1 Σ + u , and E , F 1 Σ + g singlet states of molecular hydrogen from all v i = 0 – 14 vibrational levels of the ground X 1 Σ + g state. Calculations are performed using the adiabatic-nuclei convergent close-coupling method formulated in prolate spheroidal coordinates from threshold to 500 eV. Agreement with previous calculations varies with transition and impact energy, ranging from excellent to poor. Agreement with available experiment is generally good.